Informal Sector - Harker, C. (2017)
The informal sector designates forms of paid labor that are outside, or are placed beyond, legislative and regulatory frameworks, which designate the formal sector. The crude binary between formal and informal has subsequently been nuanced, leading to the concept of dynamic and heterogeneous informal economies, and more broadly informality, a heuristic for identifying performative divisions of illegitimacy/legitimacy that constitute inter alia practices of dwelling, urbanization, and citizenship.
EPrint Processing Status: Author notified that they need to ask publisher for permission to deposit full text